The Depiction of African American Maids vs The White Socialites on The Help (2011) - Bakti Abdillah Putra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This research paper aims to investigate the contrasts in the relationship of two racial entities in the United States, African American maids and the White socialites, particularly in the segregation era (1960s). Findings and criteria of analysis were drawn from a movie called The Help (2011) with Peirce’s semiotic approach and descriptive method. Based on the observation during movie screening and literature review, the root problem happening between two groups is the disparity of previledge and socioeconomic status based on race. Besides the intangible background, signs of segregation also appeared in the movie, such as Confederate Flag of Mississippi, separate toilets, and the attires. That context demonstrates that the white socialites have stronger position over the African American maids in which the white socialites appeared as the rich and good-looking employers who treated the maids with unequal acts and accusations. This situation has not ceased to exist in real life as in American society especially when it is supported by hate and, also, government policy.